Validity and reliability of peer-grading in in-service teacher training - Foschi, Laura Carlotta; Cecchinato, Graziano (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
This paper aims to investigate the validity and reliability of peer-grading in in-service teacher training, a field where this practice has been little explored. The study has examined the peer-grading results in an inservice teacher training course involving high school teachers. The validity was measured by using the similarity between peer-grading and trainer-grading scores calculated by the Pearson correlation coefficient; while the reliability was measured by using the agreement of scores given by multiple peer graders calculated by the intraclass correlation coefficient. The empirical findings indicate that in-training teachers provided scores similar to those of the course trainers as well as fairly consistent grading results, thus highlighting that peer-generated grades seems to be valid and reliable in the field of in-service teacher training.